Eliminating Healthcare Disparities in America Beyond the IOM Report - Williams, Richard Allen (Humana Press : Imprint: Humana, 2007)
In Eliminating Healthcare Disparities in America, Dr. Richard Allen Williams assembles the very best scholars on healthcare disparities to raise the public consciousness of this issue. These experts provide the benefits of their experience and expertise as a resource for helping others to make judicious determinations about how to proceed in efforts to improve the disparities in American healthcare. Arranged into discrete categories, this volume contains comprehensive coverage, both historical and current, of the healthcare disparity crisis currently plaguing our country in hopes of leading us all to a brighter future. The volume includes chapters of examples that are currently working and concludes with recommendations on how to move forward. The text is not intended to be one in which all of the answers are given to the multitude of problems. Instead, Eliminating Healthcare Disparities in America is intended to raise the reader's level of consciousness and concern and to increase the knowledge base about the issues. This groundbreaking text will be an initial spark that ignites the fire that may one day eliminate healthcare disparities in communities around the country.